Perbandingan dan Pengaruh Penyimpanan Sampel Serum Terhadap Kualitas DNA: Pengamatan Selama 1 Tahun - Tiara Mayang P. Lio; Sanatang Sanatang; Aldiana Aldiana (University of Halu Oleo, 2021)
Molecular diagnosis is a method of diagnosis that aims to understand the molecular mechanism of a disease in each individual patient (personalized medicine / dentistry) as well as the identification process in the forensic field. This method will be very beneficial in this modern world of health. One of the molecular identification techniques that can be used as a means is the DNA amplification technique using the PCR method. This technique is able to multiply the DNA strand of the sample so that it can be analyzed more clearly. Where in the process good DNA quality can be obtained from good samples too. This is a basic requirement that must be met in molecular studies, especially in DNA fingerprinting, whereas in field practice unexpected things often occur either in the sample collection process or the availability of chemicals which result in a delay in a DNA extraction process. While the long storage time can cause damage to blood cells including DNA due to natural degradation or by microorganisms (fungi and bacteria). Comparative study and the effect of storage of serum samples on DNA quality: Observation for 1 year was a descriptive analytic study to see whether there was an effect of storage at -40C on DNA quality. This study used an analytic observational method with a cross-sectional approach. The research sample was blood serum. Genetic analysis is performed by isolating DNA from serum using routine procedures. Based on the research results, it was found that the Sig. DNA levels in 2019 and 2020 were 0.018 and the Sig. DNA purity in 2019 and 2020 was 0.00. This shows the effect of 1 year storage time on the quality of DNA from blood serum samples.